Czech Republic : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultations highlights that following a period of inaction on the structural front and a protracted recession, economic growth in the Czech Republic has picked up. Underlying this performance have been supportive macroeconomic policies, large foreign direct investment, and steady progress with structural reform. However, enterprise restructuring has led to rising structural unemployment and large regional disparities in unemployment rates. Sizable losses were accumulated by banks, which had to be transferred to the government to allow the banks to be sold to strategic investors, adding to medium-term fiscal pressures.